What is the global causality between geopolitical risks, government governance, and energy transition? Empirical evidence from cross-country data - Haijie Wang; Tianyi Zhang; Zhenhua Zhang; Yanchao Feng (Carbon Balance and Management)
Abstract Amid profound shifts in the global energy landscape, increasing attention is being paid to the causal relationships among geopolitical risks, government governance, and energy transition. Based on data covering 39 countries from 2002 to 2020, this study explores the long-term causal relationships between geopolitical risks, governance quality, and energy transition. The analysis applies cross-sectional dependence and slope heterogeneity tests, the CADF unit root test, second-generation cointegration methods, Pooled Mean Group (PMG) estimation, Method of Moments Quantile Regression (MMQR), and Granger causality tests. The results yield three key findings. Firstly, governance quality is negatively associated with energy transition, while geopolitical risks have a positive effect. Secondly, MMQR shows that these effects are more pronounced at higher quantiles of the energy transition distribution, meaning countries further along in the transition process are more responsive to changes in governance and geopolitical conditions. Thirdly, heterogeneity tests indicate that geopolitical risks exhibit a more pronounced long-term positive contribution to energy transition in economically high-growth and highly urbanized countries. These findings challenge dominant assumptions in the literature, particularly the presumed uniformly positive role of governance. The results suggest that the influence of governance and geopolitical risks on energy transition is context-dependent and nonlinear. This study provides new empirical evidence and theoretical insights to inform energy policy under geopolitical uncertainty.